Integrative multi-omics summary-based mendelian randomization identifies key oxidative stress-related genes as therapeutic targets for atrial fibrillation and flutter - Chen, Shijian; Sun, Junlong; Wen, Wen; Chen, Zhenfeng; Yu, Ziheng (Frontiers in Genetics, 2024)
At the DNA methylation level, 19 CpG sites near 7 unique genes were found to have causal effects on AF and strong co-localization evidence support (PPH4 > 0.70). At the gene expression level, six oxidative stress-related genes from eQTLGen and three from GTEx (v8), including TNFSF10, CDKN1A, ALOX15, TTN, PTK2, ALB, KCNJ5, and CASQ2, were found to have causal effects on AF in the sensitivity and co-localization analyses (PPH4 > 0.50). At the circulating protein level, both ALAD (OR 0.898, 95% CI 0.845-0.954, PPH4 = 0.67) and APOH (OR 0.896, 95% CI 0.844-0.952, PPH4 = 0.93) were associated with a lower risk of AF, and APOH was validated in the replication group. After integrating the multi-omics data between mQTL and eQTL, we identified two oxidative stress-related genes, TTN and CASQ2. The methylation of cg09915519 and cg10087519 in TTN was associated with higher expression of TTN and a lower risk of AF, which aligns with the negative effect of TTN gene expression on AF risk. TTN may play a protective role in AF.This study identified several OS-related genes, particularly TTN, as having causal roles in AF, which were verified across three-omics pathways. The findings underscore the importance of these genes in AF pathogenesis and highlight their potential as therapeutic targets. The integration of multi-omics data provides a comprehensive understanding of the molecular mechanisms underlying AF, paving the way for targeted therapeutic strategies.